How Epistemic Beliefs about Climate Change Predict Climate Change Conspiracy Beliefs - Nöth, Linnea; Zander, Lysann (Frontiers in Psychology, 2025)
Belief in climate change conspiracy theories (CCCT) can undermine support for measures against climate change. In two studies, we therefore aim to gain a clearer understanding of the factors that contribute to CCCT. A significant factor associated with CCCT is distrust in science, which is also correlated with epistemic beliefs (EBs) (e.g., beliefs are about the nature of knowledge and the process of knowing). EBs influence how individuals respond to knowledge claims, address contradictory evidence, and integrate new information. We hypothesize that EBs are linked to belief in CCCT via distrust in science. To test this hypothesis, we conducted one correlational study and one experimental study (n = 404 and n = 104, both pre-registered). Study 1 found that participants were more likely to endorse climate-related conspiracy beliefs if they viewed climate knowledge as tentative, relied on intuition to understand climate change, and had weaker beliefs in the interconnectedness of climate knowledge and its reliance on experts and scientific sources. As anticipated, distrust in climate science significantly mediated the relationships between the EBs subscales and belief in CCCT. Additionally, political ideology moderated the effect of believing knowledge originates from experts and science on distrust in climate science — this effect was pronounced among participants identifying with the political center while being weaker among left-wing participants. In Study 2, we were unable to establish a causal relationship between certainty beliefs and belief in CCCT. In conclusion, we suggest that educational initiatives aimed at fostering EBs may reduce science distrust and conspiracy beliefs.